The Development and Validation of RADEC Learning Model-Based Student Worksheets for Natural and Social Sciences (IPAS) Subjects - Suhendra, Indra; Sopandi, Wahyu; Saud, Udin Syaefudin; Handayani, Hany; Wiliiam, Nanda; Maulana, Yusup; Gunawan, Indra (International Conference on Elementary Education, 2024)
The RADEC learning model emerged as a revolutionary tool in Indonesian education, encouraging student engagement, self-discipline, and increased rigor. This approach enhances critical thinking skills, problem-solving abilities, communication, teamwork, and creativity in line with the needs of modern education. Study after study highlights the effectiveness of this approach in fostering active learning, understanding, and cooperation in the 21st century. However, using the RADEC model in sains education through the Lembar Kerja Peserta Didik (LKPD) creates challenges in terms of integration and growth. This study applies a systematic approach using the ADDIE model to measure and assess the validity of the LKPD based on RADEC for secondary education. The validation results confirm the validity of the LKPD and its compliance with the RADEC model, ensuring its quality and effectiveness in enhancing the learning process. Continuous teacher professional development and an adaptable learning model are crucial in meeting the needs of students' evolutionary progress. This study highlights the importance of implementing LKPD by the RADEC model to enhance learning outcomes in science classrooms and improve student performance